(untitled) (Global Journal of Management and Business Research, 2016)
Tough service conditions with high risk, relatively poor salaries, promotional avenues, frequent transfers and disruption in family life could be some of the reasons due to which the Indian Armed Forces are facing a severe manpower crunch. Setting up of pay commissions on regular basis to review pay structure, by up gradation of some of the ranks and appointment have also not been able to create a sense of wellbeing. Effective recruitment, competitive compensation, efficient training and development to retain the manpower available, has therefore become a greater challenge to the military leaders. This research was undertaken to analyse relevance of Best human resource practices prevalent in the corporate sector and their application in Indian Defence Organisation to assist Armed forces in attracting and retaining the best talent.